2016
DOI: 10.1038/nphys3863
|View full text |Cite
|
Sign up to set email alerts
|

Observation of quantum Hawking radiation and its entanglement in an analogue black hole

Abstract: prediction of the field is that of Hawking radiation 2 , 3 . By making an approximation to the stillunknown laws of quantum gravity, Hawking predicted that the horizon of the black hole should emit a thermal distribution of particles. Furthermore, each Hawking particle should be entangled with a partner particle falling into the black hole. This presents a puzzle of information loss, and even the unitarity of quantum mechanics falls into question 4 -6 .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
678
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 537 publications
(702 citation statements)
references
References 45 publications
21
678
2
1
Order By: Relevance
“…(55), A ωl is the reflection amplitude [see Eq. (14)] of the upcoming scalar field mode determined by the effective potential (12). For a given l, the effective potential peaks around r à ¼ 2M with its maximum depending on l (higher for larger l).…”
Section: Qnm As Multimode Squeezermentioning
confidence: 99%
See 1 more Smart Citation
“…(55), A ωl is the reflection amplitude [see Eq. (14)] of the upcoming scalar field mode determined by the effective potential (12). For a given l, the effective potential peaks around r à ¼ 2M with its maximum depending on l (higher for larger l).…”
Section: Qnm As Multimode Squeezermentioning
confidence: 99%
“…Well-known examples include the superradiance from a rotating black hole [6][7][8], the Unruh-Davies [9,10] radiation observed by a uniformly accelerated observer, and the Hawking radiation from a Schwarzschild black hole [11]. Although Hawking particles were observed in an analogue system recently [12], detection of Hawking radiation from a real black hole remains elusive because the temperature of a solar mass black hole (10 −8°K ) is much lower than the temperature of the CMB (∼2.7°K).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar configuration, the analogue of self-amplifying Hawking radiation (the so-called black-hole laser [21]) has been also observed although the interpretation of the results of that experiment is still under some controversy [22][23][24]. Finally, the observation was recently reported of the spontaneous emission of Hawking radiation by a sonic horizon through the detection of its entanglement properties [25], which constitutes the first experimental evidence of the (analog) Hawking effect.…”
Section: Introductionmentioning
confidence: 92%
“…While the Hawking radiation is quantitatively robust as long as the BH temperature is far below the energy scale characteristic of this short distance physics [20][21][22][23], its qualitative features persist even for extremely sharp horizons [14,24]. Pioneering experimental studies of this Hawking radiation have been recently reported [25].…”
Section: Introductionmentioning
confidence: 99%